An improvement of criteria for assessing the quality of clay raw material for architectural and construction ceramics - Shchukina, Lyudmyla; Galushka, Yaroslav; Bohdanova, Kateryna (Технологічний Центр, 2018)
The study analyzes the existing methods for assessing the suitability of clay raw materials for the production of architectural and construction ceramics and substantiates the need for their improvement in the direction of developing an indicator based on an analysis of the mineral composition of clays. Using the compositions of the kaolinite – montmorillonite – hydromica – quartz system, which simulate the composition of polymineral clays, the effect of clay-forming minerals and quartz impurities on the properties of the clinker ceramic materials has been established. It has been determined that the montmorillonite component of the compositions has a positive effect on the water absorption of materials, and kaolinite produces a favourable effect on the mechanical strength and frost resistance. The increase in the content of quartz in the composition of compositions from 30 % to 50 % leads to an increase in water absorption of materials, reducing their strength and frost resistance to a level unacceptable for ceramic clinker. It has been established that to obtain clinker ceramics, the quartz content in the compositions cannot exceed 40 %. A diagram of the mineral composition was developed, clearly illustrating the ratios of the main rock-forming minerals in clays with a quartz content of 30 % and 40 %, acceptable for the production of modern clinker products. The diagram shows areas of the mineral composition of clays suitable for the production of facing, paving and road clinker of the M200–300 grades and road clinker of the M400 grade at a firing temperature of 1,100 °С. The diagram of the mineral composition complements the existing indicators of the suitability of clay raw materials for the production of architectural and construction ceramics and can serve as an additional criterion for assessing their technological quality. The diagram can be used to analyze the suitability of clays for the production of ceramic clinker, provided that only the mineral composition of clays is determined without establishing their chemical and particle size distribution.

В роботі проаналізовані існуючі методи оцінки придатності глинистої сировини для виробництва архітектурно-будівельної кераміки та обґрунтована необхідність їх удосконалення в напрямку розроблення показника, заснованого на аналізі мінерального складу глин. З використанням композицій системи «каолініт  монтморилоніт – гідрослюда – кварц», які моделюють склад полімінеральних глин, встановлений вплив глиноутворюючих мінералів і домішок кварцу на властивості клінкерних керамічних матеріалів. Визначено, що позитивний вплив на водопоглинання матеріалів чинить монтморилонітові складова композицій, а на механічну міцність і морозостійкість – каолінітова. Збільшення вмісту кварцу у складі композицій від 30 % до 50 % приводить до зростання водопоглинання матеріалів, зниження їх механічної міцності і морозостійкості до рівня, неприйнятного для керамічного клінкеру. Встановлено, що для отримання клінкерної кераміки вміст кварцу в композиціях не може перевищувати 40 %. Розроблена діаграма мінерального складу, яка наочно ілюструє співвідношення основних породоутворюючих мінералів у глинах із вмістом в них 30 % і 40 % кварцу, допустимі для отримання сучасної клінкерної продукції. На діаграмі виділені області мінерального складу глин, придатних для виробництва фасадного, тротуарного і дорожнього клінкеру марок М200–300, а також дорожнього клінкеру марки М400 за температури випалу 1100 оС. Діаграма мінерального складу доповнює існуючі показники придатності глинистої сировини для виробництва архітектурно-будівельної кераміки і може служити додатковим критерієм їх технологічної якості. Діаграма може застосовуватися для аналізу придатності глинистої сировини для виробництва керамічного клінкеру за умови визначення лише мінерального складу глин без встановлення їх хімічного і гранулометричного складу.
Keywords: architectural and construction ceramics; clinker materials; polymineral clay; criteria of technological quality; industrial application/use; архітектурно-будівельна кераміка; клінкерні матеріали; полімінеральні глини; критерії технологічної якості; промислове використання